Integrated decoys and effector traps: how to catch a plant pathogen. Issue 1 (December 2016) - Ellis, Jeffrey
Abstract Plant immune receptors involved in disease resistance and crop protection are related to the animal Nod-like receptor (NLR) class, and recognise the virulence effectors of plant pathogens, whereby they arm the plant's defensive response. Although plant NLRs mainly contain three protein domains, about 10 % of these receptors identified by extensive cross-plant species data base searches have now been shown to include novel and highly variable integrated domains, some of which have been shown to detect pathogen effectors by direct interaction. Sarris et al. have identified a large number of integrated domains that can be used to detect effector targets in host plant proteomes and identify unknown pathogen effectors. Please see related Research article: Comparative analysis of plant immune receptor architectures uncovers host proteins likely targeted by pathogens, http://dx.doi.org/10.1186/s12915-016-0228-7 Since the time of writing, a closely related paper has been released: Kroj T, Chanclud E, Michel-Romiti C, Grand X, Morel J-B. Integration of decoy domains derived from protein targets of pathogen effectors into plant immune receptors is widespread. New Phytol. 2016 (ahead of print)